Adoption of pets in distributed network using blockchain technology. (7th August 2020) - Gururaj, H.L.; Manoj, Athreya A.; Kumar, Ashwin A.; Nagarajath, S.M.; Kumar, V. Ravi
As the whole world is moving towards digital payments, ethers and the transaction methods with quick payment features are stored in a blockchain in a distributed network. To adopt pet animals, this technology provides security and flexibility to users. The distributed network is a network system through which data, software and computer programming are spread across on more than one node(computers) and these nodes are dependent on each other. It is nothing but a peer-to-peer network which eliminates a single point of failure. The blockchain is a growing list of records called blocks, that are linked using cryptography. It is a decentralised, distributed and an immutable ledger to store digital transactions. Its databases are managed using a peer-to-peer network where all the nodes in a network are equal and are the major concern in the types of network architecture. The consensus protocol is used for transacting and communicating between the nodes. In this paper, a unique way of adopting pets is proposed where the transaction details are stored in a blockchain whereby using hash value returns further details of the transaction. It provides users more convenient access in adopting pets and provides a better approach to the existing centralised system.